Photoresponsive polymers and block copolymers by molecular recognition based on multiple hydrogen bonds. Issue 22 (30th August 2014) - Concellón, Alberto; Blasco, Eva; Piñol, Milagros; Oriol, Luis; Díez, Isabel; Berges, Cristina; Sánchez‐Somolinos, Carlos; Alcalá, Rafael
ABSTRACT A new methacrylate containing a 2, 6‐diacylaminopyridine (DAP) group was synthesized and polymerized via RAFT polymerization to prepare homopolymethacrylates (PDAP) and diblock copolymers combined with a poly(methyl methacrylate) block (PMMA‐b‐PDAP). These polymers can be easily complexed with azobenzene chromophores having thymine (tAZO) or carboxylic groups with a dendritic structure (dAZO), which can form either three or two hydrogen bonds with the DAP groups, respectively. The supramolecular polymers were characterized by spectroscopic techniques, optical microscopy, TGA, and DSC. The supramolecular polymers and block copolymers with dAZO exhibited mesomorphic properties meanwhile with tAZO are amorphous materials. The response of the supramolecular polymers to irradiation with linearly polarized light was also investigated founding that stable optical anisotropy can be photoinduced in all the materials although higher values of birefringence and dichroism were obtained in polymers containing the dendrimeric chromophore dAZO. © 2014 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 3173–3184